Miguelito ang batang rebelde - Brocka, Lino 1939-1991; Dalisay, Jose Y.; Muhlach, Aga; Garcia, Eddie; Blanca, Nida; Romero, Gloria; Razon, Delia; Barreto, Gretchen (Award winning home grown movie, 2003)
Mayor Ven Herera is grooming his only son Miguelito "Mike" Herera to be his predecessor. Mike, however, has other plans and live a happy go lucky life.